The Effect of social media usage on employee performance at the Gambia Ports Authority - Manneh, Aida Kombeh; Badjie, Gibriel; Saminaka, Tanimu Umaru (Universitas Nusantara PGRI Kediri, 2025)
Design/Methode/Approach: The study used a quantitative-survey research strategy getting information from individuals within GPA. Analysis of the data was conducted using the Statistical Package for Social Sciences (SPSS) analytical and SmartPLS tool. Research Finding: The hypothesis is supported which in turn indicates the path is significant between the independent and dependent variable. H1 (0.547, p < 0.05) describes the path between social media usage and employee performance. Theoretical contribution/Originality: The study revealed the necessity for GPA to adopt social media as a strategic communication tool for efficient dissemination of information within the organization and a means to empower employees. Theoretically, informed employees are more involved and engaged to serve the organisation. Practical/Policy implication: The study will aid the implementation of a social media policy which will serve as a policy document to guide staff on how and when to use social media during official work hours. Research limitation: The findings of the study cannot be generalized with other SOEs as the study is limited to Gambia Ports Authority only. Keywords: Social Media, Gambia Ports Authority, Employee Performance.